Cyst decreased in size post maxillary sinus floor augmentation surgery in diabetic patient: A case report. (2015) - Zhang, Sijia; Song, Yingliang; Wei, Hongbo; Ren, Shuai
Highlights: 2.37 mm from the ridge to sinus floor with cyst (18.72 mm × 24.61 mm) firmly attached to the wall. Lateral approach to elevate the sinus floor with cyst simultaneously in diabetic patient. Osseointegration was achieved and the cyst decreased in size 6 months later. Abstract: Introduction: Whether mucosal cyst of maxillary sinus is contraindication for sinus floor augmentation surgery has been a controversial hot spot for years. Presentation of case: This case aims to present the surgical procedure of sinus floor augmentation surgery with cyst (18.72 mm × 24.61 mm) in diabetic patient. And 6 months later, the cyst decreased in size. The authors elevated the sinus floor and cyst simultaneously. The surgery was carried out successfully without sinus membrane perforation and the alveolar ridge gained about 8 mm height. Six months later, the cyst decreased in size and osseointegration was observed. Discussion: Interdisciplinary cooperation is encouraged to diagnose benign mucosal cyst. The isolation between sinus lumen and the grafted sub-sinus space is important. Graft contamination or dispersion into the sinus lumen should be avoided. The integrity of the sinus membrane and use of antibiotics are very important to prevent the occurrence of postoperative sinus infection Conclusion: The authors conclude that sinus augmentation surgery could be done with mucosal cyst in diabetic patient.